Judgement or Vindication? Deuteronomy 32 in Hebrews 10:30 - Proctor, John (Tyndale bulletin, 2004)
There is a case for the translation ‘vindicate’ rather than ‘judge’ in Hebrews 10:30, which is itself a biblical quotation from Deuteronomy 32. Four arguments contribute. The first is lexical: the verb κρίνω often does mean ‘vindicate’ in the LXX. The second is intertextual: Hebrews adopts Deuteronomy sensitively, and Deuteronomy has vindication in view. The third is text-critical: an unusual text-form in Hebrews raises the possibility that targumic readings may have insight to give. The fourth is rhetorical: the reading ‘vindicate’ sharpens our awareness of the author’s persuasive strategy in this part of Hebrews.